Women’s authorship and Costa Rican literature (1845-1888) - Molina Jiménez, Iván (2024)
Was print authorship culture out of reach for women before 1887 in Costa Rica? The main purpose of this article is to offer a first answer to this question based on a preliminary review of newspapers and magazines that allow considering the problem from a broader perspective. Briefly, the central argument that is going to be developed is that the construction of this authorship went through three stages: in the first, during the 1840s and 1850s, this process was based on the writing of commercial advertisements; in the second, focused on the 1860s and 1870s, the discourses of female students and teachers related to teaching activities predominated; and in the third, located from 1885, there were two parallel trends. On the one hand, some teachers began to publicize their literary productions; and on the other, the State, on the eve of the educational reform of 1886, implemented a policy for educators to prepare reports on their school activities and send them to a specialized magazine to be published.